Photocatalytic activity of magnetic core-shell CoFe2O4@ZnO nanoparticles for purification of methylene blue - Edi Suharyadi; Afifah Muzakki; Astrie Nofrianti; Nurul Imani Istiqomah; Takeshi Kato; Satoshi Iwata (Materials Research Express, 2020)
Magnetic core–shell CoFe _2 O _4 @ZnO nanoparticles have been successfully synthesized by using coprecipitation method to provide easy separated nanomaterials and high photocatalytic activity performance. Core–shell nanoparticles with various CoFe _2 O _4 -to-ZnO molar ratio (1:2, 1:3, 1:4, 1:5) have been investigated over x-ray diffraction (XRD), transmission electron microscopy (TEM), UV-visible spectroscopy, and vibrating sample magnetometer. XRD spectra confirm the cubic spinel ferrite phase structure of CoFe _2 O _4 and the hexagonal wurtzite phase of ZnO. The crystallite size is found within the range of 14.9–20.6 nm. TEM measurement confirms the good crystallinity of the samples. The magnetic hysteresis shows that CoFe _2 O _4 @ZnO has high saturation magnetization of about 30 emu g ^−1 and coercivity of about 300 Oe. Photocatalytic investigation was carried out using methylene blue (MB) under UV irradiation. Our result yields the enhancement of MB degradation as ZnO content increases. The maximum photodegradation achieved by the core–shell nanoparticles is 57.2%, 60.5%, 65.5%, and 78.3% for molar ratio of 1:2, 1:3, 1:4, and 1:5, respectively. The enhancement of MB degradation can be attributed to the formation of internal structure between CoFe _2 O _4 and ZnO in the form of heterojunction structure. The magnetic properties of core–shell lead to the easy separation between the magnetic core–shell nanoparticles and the final degraded solution by permanent magnet.